Thermal behavior, liquid crystalline properties and fatty acid profile of lipids from irradiated chicken meat - Rosales, Czarina Kristine S. (2004)
ABSTRACT Changes in the characteristics of chicken lipids were analyzed as a means to determine irradiation. The Bligh and Dyer method was used to extract the lipid components of the frozen ground chicken meat irradiated using Cobalt-60 and of the control. The thermal behavior, liquid crystalline properties and fatty acid composition of the extracted lipids were determined using Differential Scanning Calorimetry (DSC), Optical Polarizing Microscopy (OPM) and Gas Chromatography (GC), respectively, to differentiate the treated from untreated specimens. The DSC thermograms for the lipids from the non-irradiated samples show two peaks occurring at approximately 15.78 ± 0.49°C and 25.35 ± 0.78°C. Two peak temperatures were also detected in the irradiated samples at about 15.98 ± 1.40°C and 32.37 ± 4.49°C. Distinctive liquid crystalline formations were exhibited by the non-irradiated chicken lipids but were absent in the irradiated samples. The amounts of lauric, myristic, myristoleic, palmitic, stearic and oleic acids increased in the irradiated chicken lipids while a reduction in the amounts of capric, palmitoleic, linoleic and linolenic acids was observed. These variations in fatty acid profile may have caused the changes identified in the thermal behavior and liquid crystalline formations of the samples. The combined use of DSC and OPM has a great potential for irradiation exposure determination, as verified by GC an